Exploring the perception of English lecturers about incidental vocabulary learning and involvement load hypothesis in their classrooms - Saputro, Teguh Hadi; Hima, Aninda Nidhommil; Prastiyowati, Santi (Universitas Islam Negeri Palangka Raya, Indonesia, 2024)
Despite extensive research on vocabulary acquisition, limited attention has been given to how these theories are applied in English as a foreign language (EFL) teaching practices, particularly in Indonesia. This qualitative case study addresses this gap by exploring English lecturers' perceptions and use of incidental vocabulary learning (IVL) and the involvement load hypothesis (ILH) in their classrooms. Data were collected through interviews and classroom observations with five English lecturers from universities in Malang, Indonesia, and analyzed using thematic analysis to identify key patterns and themes. The findings revealed that all participants recognized the importance of vocabulary in language learning and preferred implicit learning methods, such as exposure to authentic language in literature and films. However, the integration of theoretical concepts like vocabulary size and frequency into teaching practices was limited due to constraints such as time and lack of dedicated vocabulary instruction. Moreover, participants were unfamiliar with the ILH, though some of its elements were present in their teaching. The study suggests that better dissemination of research and professional development is essential to bridge the gap between theory and practice, ultimately improving vocabulary instruction in EFL contexts.